MENELAAH ULANG POLIGAMI DALAM HUKUM PERKAWINAN - Ali Imron (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2015)
Marriageis essentially areunification ofmen and womenconsistingof elements ofsouland body arefusedinto one inahouseholdframeforemotional and physicalwelfare. Regulationof marriageembracedthe principlethata manmay onlyhavea wifeand vice versa. The court maygrant permissionto the husbandtoa wifemorethanacertain requirements.QualitativeandquantitativeJusticeas a condition ofpolygamydifficultand evenimpossible to berealized. Polygamy issynonymouswiththe exploitation ofwomenfor the sake ofgreedandsexuallust.